Encapsulation of Co3O4 Nanoparticles Inside CeO2 Nanotubes: An Efficient Biocatalyst for the Ultrasensitive Detection of Ascorbic Acid. (4th July 2018) - Zhu, Yun; Yang, Zezhou; Song, Lifei; Chi, Maoqiang; Li, Meixuan; Wang, Ce; Lu, Xiaofeng
Abstract: A quick and sensitive detection of ascorbic acid (AA) is essential in the fields of biosensing and disease diagnosis. In this work, an effective approach combined with electrospinning, chemical bath deposition, and calcination process is developed to encapsulate Co3 O4 nanoparticle into CeO2 nanotubes as efficient peroxidase mimics for the detection of AA. The peroxidase‐like catalytic activity of the as‐prepared Co3 O4 @CeO2 nanotubes is much higher than that of individual Co3 O4 nanofibers and CeO2 nanotubes alone due to the synergistic effect between the two components. Owing to the superior catalytic efficiency of the prepared Co3 O4 @CeO2 nanotubes, a colorimetric route for the rapid and accurate detection of AA with a detection limit of 0.73 × 10 −9 m with a wide linear range from 0 to 0.8 × 10 −6 m is demonstrated. This detection limit is much better than the previous reports based on the enzyme‐like catalytic systems. In addition, a good selectivity toward the detection of AA over amino acids, common ions, dopamine, and uric acid is achieved. This study offers a new approach for the fabrication of Co3 O4 @CeO2 nanotubes as sensing platform toward the detection of AA, which presents promising potential applications in biosensing, environmental monitoring, and medical diagnostics. Abstract : Co3 O4 nanoparticles are encapsulated inside CeO2 nanotubes as peroxidase mimics which could be used for the ultrasensitive detection of ascorbic acid.